Handling Children with Speech Delay: Can Therapy Using the Storytelling Method Treat it? - Imam Tabroni; Rini Purnama Sari; Hance Ayu Ningrum; Rizqotul Maula; Sopiatul Munawaroh; Marisa Marisa (Yayasan Adra Karima Hubbi, 2024)
Children's delays in speaking are influenced by two factors; genetics and environment. Environmental factors can be overcome with learning therapy using the storytelling method. The habit of telling stories provides strong stimulation to stimulate children to participate in conversations consistently. The research process was carried out by looking at the learning process of early childhood using the storytelling method. What the teacher does is fully supported by the school principal and education staff to jointly develop the habit of telling stories for children with special needs who are delayed in speaking. The research results show an increase in vocabulary and sentences in the last few months. Greetings, greetings and responsiveness have begun to appear, although the development is not consistent. Counting twice a week, speech-delayed children show interest and come up with new vocabulary which is an emphasized storytelling activity. Sometimes there is no vocabulary development in a whole week.